Sexual abuse in the Catholic Church: How to respond to demands for justice? (2018)
Child sexual abuse in the Catholic Church is a problem of great dimensions and universal scope. The model of restorative transitional justice allows an adequate approach, given the limitations of the criminal justice system to respond to the needs and rig